A Treatise on Probability - Keynes, John Maynard, 1883-1946 (Salt Lake City, UT : Project Gutenberg, 2010)
"A Treatise on Probability" by John Maynard Keynes is a philosophical work published in 1921. It presents a groundbreaking logical approach to uncertainty, moving beyond traditional numerical probability theories. Keynes argues that probability is a logical relationship between evidence and hypothesis$1 (Bone that isn't always quantifiable or comparable. Through examining fundamental concepts, measurement challenges, and the weight of evidence, he develops a framework that influenced later thinkers and remains relevant to modern artificial intelligence and behavioral economics debates. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Treatise_on_Probability
Release date is 2010-05-31
Keywords: Probabilities